Developing and planning country-specific integrated knowledge translation strategies: experiences from the GELA project in Malawi, Nigeria, and South Africa - Bey-Marrié Schmidt; D. Mabetha; M. Chibuzor; G. Kunje; D. Arikpo; E. Aquaisua; S. Lakudzala; N. Mbeye; E. Effa; S. Cooper; T. Kredo (BMC, 2024)
Abstract Background The Global Evidence, Local Adaptation (GELA) project aims to maximise the impact of research on poverty-related diseases by increasing researchers' and decision-makers' capacity to use global research to develop locally relevant guidelines for newborn and child health in Malawi, Nigeria and South Africa. To facilitate ongoing collaboration with stakeholders, we adopted an Integrated Knowledge Translation (IKT) approach within GELA. Given limited research on IKT in African settings, we documented our team's IKT capacity and skills, and process and experiences with developing and implementing IKT in these countries. Methods Six IKT champions and a coordinator formed the GELA IKT Working Group. We gathered data on our baseline IKT competencies and processes within GELA, and opportunities, challenges and lessons learned, from April 2022 to March 2023 (Year 1). Data was collected from five two-hour Working Group meetings (notes, presentation slides and video recordings); [2] process documents (flowcharts and templates); and [3] an open-ended questionnaire. Data was analysed using a thematic analysis approach. Results Three overarching themes were identified: [1] IKT approach applied within GELA [2], the capacity and motivations of IKT champions, and [3] the experiences with applying the GELA IKT approach in the three countries. IKT champions and country teams adopted an iterative approach to carry out a comprehensive mapping of stakeholders, determine stakeholders' level of interest in and influence on GELA using the Power-Interest Matrix, and identify realistic indicators for monitoring the country-specific strategies. IKT champions displayed varying capacities, strong motivation, and they engaged in skills development activities. Country teams leveraged existing relationships with their National Ministries of Health to drive responses and participation by other stakeholders, and adopted variable communication modes (e.g. email, phone calls, social media) for optimal engagement. Flexibility in managing competing interests and priorities ensured optimal participation by stakeholders, although the time and resources required by IKT champions were frequently underestimated. Conclusions The intentional, systematic, and contextualized IKT approach carried out in the three African countries within GELA, provides important insights for enhancing the implementation, feasibility and effectiveness of other IKT initiatives in Africa and similar low- and middle-income country (LMIC) settings.